ANALISIS YURIDIS PEMIDANAAN TERHADAP TAX EVASION DAN TAX AVOIDANCE (STUDI KASUS PANAMA PAPERS) - Danyathi, Ayu Putu Laksmi; Putra, I Made Walesa (VYAVAHARA DUTA, 2020)
Taxes are mandatory contributions from taxpayers to the state which are compelling based on Constitution without receiving direct compensation, in addition; taxes are used for the greatest prosperity of the people.However, there were allegations of irregularities in the tax sector in the case of the leak of the Panama Papers documents. Several businessmen, leaders and state officials were mentioned on Panama Papers, including those who come from Indonesia. Various motives or backgrounds for their participation on Panama Papers, so that it was suspected there were allegations of tax evasion and tax avoidance. Based on those allegations, the question that arose was whether participation on the Panama Papers is Tax Evasion and or Tax Avoidance and how the national criminal law is regulated in this regard. The type of research used is normative research, namely legal research which is carried out based on the norms and principles of the laws and regulations related to tax crime.The result of the research showed that the case study Panama Papers case can be classified as tax evasion because the indication leads to the embezzlement of tax. Even if it is classified as tax avoidance, the perpetrator should still have moral responsibility because tax avoidance is actually a smuggling law (in fact, it is not in accordance with the philosophy of the tax law passed).   Keywords: Juridical analysis, The Punishment, Tax Evasion, Tax Avoidance